IMPLEMENTASI EKONOMI SIRKULAR PADA SEKTOR PENGELOLAAN SAMPAH DI KAWASAN ASIA TENGGARA - Sahrani, Sarah; Hotimah, Oot; Habibah, Siti; Sabitha, Talitha (Jurnal Geografi, 2024)
Countries in Southeast Asia tend to still use a linear economic system, where the economic system continues to experience losses. This has made countries in Southeast Asia start planning to change their linear economic system to a circular economy. A circular economic system has the principle of sustainably maintaining the value of products, materials and resources in the economy, thereby generating economic growth. The research method used is literature review or literature study, namely by searching for data related to the discussion in the research title that the researcher took. The research results show that countries in Southeast Asia such as Thailand, the Philippines, Indonesia, Singapore and Malaysia are starting to plan and implement a circular economy system in the waste management sector to ensure waste reduction and sustainable waste management.